AB0846 Personalising care: using infliximab drug trough and anti-drug antibody levels improves clinical treatment decisions and is a cost effective strategy in spondyloarthritis. (12th June 2018) - Dubash, S.; Bryer, D.; Fitton, J.; Barr, A.; Vandevelde, C.; Marzo-Ortega, H.; Freeston, J.
Abstract : Background: Personalised medicine tailors treatment to the individual's needs. The advent of biosimilars has led to therapy re-appraisals driven by healthcare commissioning bodies' demand forcost-effective interventions. Yet, biologic drug dosing is standardised and little is known about the rationale and efficacy of dose adjustment. Objectives: As part of a service evaluation exercise, we measured serum drug trough levels (DLs) and anti-drug antibodies(ADAbs) in our cohort of patients with axial spondyloarthritis (axSpA) and Psoriatic arthritis (PsA) receiving bio-originator infliximab with the aims of a) informing our decision making upon switching to a biosimilar and b) assessing the impact of this approach to our clinical practice. Methods: Eligible subjects identified, were counselled and consented by an experienced specialist nurse on DLs and ADAb testing and possible associated outcomes including change in drug class, dose, infusion time interval and switching from bio-originator infliximab to the biosimilar infliximab CT-P13. A treatment algorithm was developed to guide the treating physician. Clinical and outcome data were recorded as per routine practice including disease status, DLs and ADAb titre, and clinical outcome. Results: We identified 53 subjects. Based upon disease activity, DL and ADAb level, bio-originator infliximab was discontinued in 3 (6%) subjects, the infusion interval was extended in 8 (15%), shortened in 3 (6%), and the dose reduced in 3 (6%) subjects. Four patients (8%) changed to an alternative biologic due to persistent high disease activity on infliximab. ADAbs were absent in 20/28 (71%) subjects on concomitant methotrexate (MTX). Very high titre ADAbs were identified in 8 (15%) subjects with corresponding very low (n=2) or undetectable (n=6) DLs suggesting likely drug-neutralisation. The total estimated cost-savings from drug discontinuation and interval extension or dose reduction were £28, 689 per annum in addition to the biosimilar switch saving of £41, 184 per annum. Conclusions: These data from a small cohort suggest that measuring ADAbs and DLs to characterise treatment response, tailor treatment regime and inform biosimilar switching is a clinically efficacious and cost-effective strategy in infliximab-treated SpA patients. We anticipate further significant savings with our cohort receiving subcutaneous therapies. This approach unlocks the potential of "personalised medicine" which supports individualised treatment and brings significant savings to the healthcare provider. Disclosure of Interest: None declared